Desastres naturais: como propor listas de medicamentos para essas situações? - Póvoa, Julia; Frota, Lucas; Matos, Guilherme; Abdon, Letícia; Alcantara, Paulo Sérgio Gonçalves de; Silva, Gabriel Fernandes da; Viana-Silva, Julia Vitória; Araujo, Letícia; D’Oliveira, Letícia da Costa Lima; Pinheiro, Sâmia Jucá; et al. (Farmacoterapêutica, 2022)
Desastres naturais: como propor listas de medicamentos para essas situações?